Vertical transmission of the human papillomavirus: a systematic quantitative review - Lidia Rosi Medeiros; Anaelena Bragança de Moraes Ethur; Juliana Balbinot Hilgert; Roselaine Ruviaro Zanini; Otávio Berwanger; Mary Clarisse Bozzetti; Luciane Calil Mylius
In order to better understand the exact mode and risk of vertical transmission in asymptomatic pregnant women, as well as the relationship between HPV transmission and mode of delivery, we have proposed this systematic quantitative review of prospective cohort studies. A comprehensive search was performed in the Cochrane Library, MEDLINE, LILACS, CANCERLIT, and EMBASE, as well as in the reference lists from the identified studies. Nine primary studies, which included 2,111 pregnant women and 2,113 newborns, met our selection criteria and were analyzed. A positive HPV test in the mother increased the risk of vertical HPV transmission (RR: 4.8; 95%CI: 2.2-10.4). We also observed a higher risk of HPV infection after vaginal delivery than after cesarean section (RR: 1.8; 95%CI: 1.3-2.4). The results of this meta-analysis showed the HPV DNA-positive rate only after birth, but an HPV DNA-positive neonatal sample does not necessarily indicate infection; it could merely indicate contamination (perinatal HPV contamination may have occurred). Infants born through vaginal delivery were at higher risk of exposure to HPV.